Literature Review : Isolation and Identification of Bacteria in Children with Respiratory Infections - Wardatul Jannah; Yusriani Mangarengi; Nurhikmawati; Yani Sodiqah; Marzelina Karim (International Journal of Health Engineering and Technology, 2025)
Background: Acute Respiratory Tract Infection (ARI) is one of the most common diseases and a leading cause of death in toddlers in Indonesia. This disease can be caused by bacteria, viruses, fungi, or aspiration. Objective: This study aims to determine the types of bacteria present in children with ARI and the most common bacteria found in children with ARI. Method: The study used a literature review with a narrative review design, where the research process started from searching in database search engines: Pubmed, NCBI, Google Scholar, then sorted related to the title of Isolation and Identification of ISPA bacteria in children in 2017-2025, The search results yielded 904 journals. The journals were re-selected based on the standard isolation method and PCR (Polymerase Chain Reaction) with keywords acute respiratory tract infection, ISPA children, ISPA bacteria children, yielding 60 journals. The next selection looked at the entire text containing tables and graphs, yielding 32 journals. Then, they were re-selected by looking at their suitability in the field of microbiology, yielding 8 journals. Results: The results of the study showed that various types of bacteria were successfully identified as the cause of ARI in children, including Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, Klebsiella pneumoniae, Pseudomonas aeruginosa, Corynebacterium diphtheriae, Moraxella catarrhalis, Bacillus sp., and Sphingomonas paucimobilis. Most studies reported that Gram-positive bacteria were more dominant, with Streptococcus pneumoniae and Staphylococcus aureus as the most common species, although Gram-negative bacteria such as Klebsiella pneumoniae and Pseudomonas aeruginosa were also found, especially in cases of severe ARI. Conclusion: This study shows that acute respiratory infections (ARI) in children are caused by various bacteria, predominantly Gram-positive. Streptococcus pneumoniae and Staphylococcus aureus are the most frequently found bacteria, while Klebsiella pneumoniae and Pseudomonas aeruginosa play a significant role in more severe cases.